Mating system and inbreeding depression in Hymenaea stigonocarpa - Zaruma, Darlin U.G. [UNESP]; Sebbenn, Alexandre M.; Rossini, Bruno C. [UNESP]; Pardo, Ana C.F. [UNESP]; Silvestre, Marcela A.M. [UNESP]; Cambuim, Jose [UNESP]; da Silva, Alexandre M. [UNESP]; Pupin, Silvelise [UNESP]; Rodrigues, Carlos J. [UNESP]; Marino, Celso L. [UNESP]; de Moraes, Mário L.T. [UNESP] (Springer Nature, 2024)
In tree species, inbreeding due to selfing or biparental mating may decrease offspring adaptation and growth due to inbreeding depression (ID). Degenerative effects of ID, mainly reduction in productivity and survival, are undesirable for ex-situ conservation, improvement, and environmental and commercial reforestation of tree species. The effects of ID resulting from self-fertilization and biparental inbreeding were assessed for the traits cylindrical volume and survival in juvenile individuals of Hymenaea stigonocarpa in a progeny test (0.83 ha) at 4 and 7 years of age. The progeny test was established for ex situ conservation in the state of Mato Grosso, Brazil, and was based on seeds collected from a wild population. Nine microsatellite loci were used to genotype 48 adult (plot = 4.3 ha) and 612 juvenile samples to determine spatial genetic structure (for adults), inbreeding, mating system, and pollen dispersal pattern. Spatial genetic structure was observed up to 82 m. Reproduction occurred mainly by outcrossing, with low rates of selfing (7.5%) and biparental inbreeding (13.2%). Mating was not random due to the fat-tail pollen dispersal pattern, resulting in high pollen immigration (70.1%) and low mean pollen dispersal distance (105 m) within the sample area. Inbreeding was observed only in juveniles, indicating selection against inbred individuals between juvenile and adult stages. The volume trait showed higher ID for biparental inbreeding (41.5–44.0%) than for self-fertilization (29.1–42.6%). Volume also showed greater ID than survival. Our results show that even low rates of selfing and biparental inbreeding can decrease the productivity of H. stigonocarpa plantations.
Keywords: Inbreeding; Mating system; Pollen flow; Savannah; Tropical trees